2017
DOI: 10.26656/fr.2017.4.056
|View full text |Cite
|
Sign up to set email alerts
|

Application of fractional factorial design to improve hot smoked Nile Perch (Lates niloticus) quality

Abstract: The aim of this research was to study the parameters influencing moisture, salt and total phenol content of hot smoked Nile Perch and to compare the influence of processing conditions on its proximate composition and sensory quality. The effect on moisture, salt and total phenol content was investigated using fractional factorial design with seven factors and two levels: X 1 for brine concentration, X 2 for brining time, X 3 for preliminary smoking-drying time, X 4 for smoking time, X 5 for hot smoking time, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The collected data was statistically analyst by fitting the first-order model with interaction terms proposed for each response variable (y i ). The empirical model in terms of coded factors was performed using the following Equation (4) (adapted from Sokamté et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The collected data was statistically analyst by fitting the first-order model with interaction terms proposed for each response variable (y i ). The empirical model in terms of coded factors was performed using the following Equation (4) (adapted from Sokamté et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that three of the investigated factors: acids (HNO3 and H2O2) volume and digestion time were most significant. Sokamte et al (2017) studied the effect of two-level seven factors: brine concentration, brining time, preliminary smoking-drying time, smoking time, hot smoking time, smoking temperature and hot smoking temperature on moisture, salt and total phenol content of hot smoked Nile Perch fish using a 2 7-3 fractional factorial design with resolution V. A combination of 16 tests and additional 4 replicates at the center point were run. For the total phenol content, only the smoking temperature was statistically significant.…”
Section: Applications Of Fractional Factorial Designmentioning
confidence: 99%